The needs of LGBTI+ people within student nurse education programmes: a new conceptualisation - Mc Cann, Edward (My University, 2020)
There is a growing body of international research evidence highlighting concerns around social exclusion and discrimination, significant health inequalities and health needs, and barriers to accessing effective healthcare for LGBTI + people. However, ways in which the healthcare needs of LGBTI + people can be addressed in student nurse education programmes have yet to be fully explored. The aim of this discussion paper is to present the evidence to support the inclusion of LGBTI + health throughout the nursing curriculum. A new conceptualisation of the full and effective integration of LGBTI + health content across and within the nursing curriculum is proposed. This can be achieved by further developing theory, skills simulation and practice learning opportunities. There is a need to ensure that nursing students are positioned and adequately prepared to effectively address concerns of social justice, reducing health inequalities, and providing responsive person-centred care for LGBTI + health service users.
PUBLISHED
Keywords: LGBT; Nursing Evidence; Social justice; Health inequalities; Nurse education; Inclusive Society; Adult Education; LGBT; LGBT+; LGBTI; LGBTQ+; Nursing Education